Bony Cyst in a Ground Glass Matrix: A Rare Case Report of Craniofacial Fibrous Dysplasia with Secondary Aneurysmal Bone Cyst - Sachar, Chandrika; Agarwal, Aakanksha; Syed, Anjum (Indian Journal of Radiology and Imaging, 2022)
Fibrous dysplasia has various ways of presentation including syndromic associations and secondary changes within the lesion. We present a case of a 21-year-old female with craniofacial fibrous dysplasia, presenting with proptosis and intermittent blurring of vision due to focal fibrous dysplasia involving the frontal bone with secondary aneurysmal bone formation that was provisionally diagnosed on imaging and confirmed on histopathology. This case demonstrates the typical imaging findings of fibrous dysplasia with seldom encountered secondary aneurysmal bone cyst formation and also discusses about the pathology and management of the craniofacial fibrous dysplasia.
Keywords: craniofacial fibrous dysplasia; secondary aneurysmal bone cyst; tumor